The institutional digital repository of the Department of Information and Library Sciences at the University of Khartoum (evaluative study) | المستودع الرقمي المؤسسي لقسم علوم المعلومات والمكتبات بجامعة الخرطوم (دراسة تقويمية) - Al-Zahrani | الزهراني, Saeed Ahmed Saeed Al-Dahiya | سعيد أحمد سعيد الدحية (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
The study aimed to introduce the institutional digital repository of the Department of Information and Library Sciences at the University of Khartoum, and its idea, vision, mission, and policies in depositing, organizing, and making digital contents available. And evaluate it by identifying the degree of acceptance it enjoys among researchers and specialists in the field of information sciences and libraries. Thus, it contributes significantly to introducing this repository, its idea, vision, mission and policies in depositing, organizing and making digital contents available, and reveals the strengths and weaknesses of this repository. The researcher hopes that this study will represent a starting point for other studies in the same field that can cover its various aspects, and produce positive results that enhance this type of research studies. | هدفت الدراسة إلى التعريف بالمستودع الرقمي المؤسسي لقسم علوم المعلومات والمكتبات بجامعة الخرطوم، وفكرته ورؤيته ورسالته وسياساته في إيداع المحتويات الرقمية وتنظيمها وإتاحتها. وتقويمه من خلال التعرف على درجة القبول التي يحظى بها من قبل الباحثين والمتخصصين في مجال علوم المعلومات والمكتبات. وهي بذلك تساهم بشكل كبير في التعريف بهذا المستودع وفكرته ورؤيته ورسالته وسياساته في إيداع المحتويات الرقمية وتنظيمها وإتاحتها، وتكشف عن مواطن القوة والضعف في هذا المستودع. ويأمل الباحث أن تُمثل هذه الدراسة نقطة انطلاق لدراسات أخرى في نفس المجال يمكن أن تُغطي جوانبه المختلفة، والخروج بنتائج إيجابية تُعزز مثل هذا النوع من الدراسات البحثية.